Facet joint syndrome treated with interventional procedures: a review article with an update on the current evidence and practice. Issue 6 (November 2020) - Valerio, Pace; Marzano, Fabrizio; Milazzo, Federico; De Larrea, Antonio Eduardo; Placella, Giacomo; Caraffa, Auro; Rinonapoli, Giuseppe
Abstract : Background: Facet Joint Syndrome (FJS) is a common progressive disease affecting small joints of the spine and can have painful symptoms. When conservative treatment measures fail, there are a wide range of interventional procedures that can be used. Varied results have been obtained with different procedures, and standardized indications and guidelines are unclear. The authors aimed to review the most current evidence on indications, utilization of interventional procedures, results, and complication risks for the treatment of FJS. Methods: Customized structured electronic searches were performed in PubMed and Cochrane databases. Meta-analyses, randomized controlled trials (RCT), and systematic reviews on FJS treated with interventional minimally invasive procedures published from 1st of January 2015 to 29th of February 2020 were included. We initially selected 320 studies, and 25 studies (two meta-analyses, six systematic reviews, and 17 RCT) were selected according to inclusion and exclusion criteria. Results: A certain amount of improvement of pain was reported in 100% of the patients, with no significant complications reported. Most studies showed efficacy of all interventional procedures at all levels of evidence, without providing definitive data on indications and superiority of one procedure over others. Conclusions: The authors suggest a standardized stepladder approach to the management of FJS, with conservative measures initially and interventional procedures if those measures fail. All procedures were reported to be safe and efficient when clinically indicated and properly performed. Further studies with appropriate methodology are needed. Level of Evidence: Level IV.